2013
DOI: 10.2166/ws.2012.082
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of dissolved organic matter and haloacetic acid formation potential in drinking water treatment by a comprehensive fractionation technique

Abstract: A comprehensive fractionation technique was applied to a set of water samples obtained along a real drinking water treatment plant with ozonation and granular activated carbon (GAC) treatment to obtain detailed profiles of dissolved organic matter (DOM) and to evaluate the haloacetic acid (HAA) formation potentials of these DOM fractions. The results indicated that ozonation and GAC treatment showed limited ability to remove hydrophilic fractions (23%), while removal of hydrophobic fractions was 72%. The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…When using granular activated carbon as the substrate in the biofilter, the intrinsic composition of the carbon backbone of activated carbon favors the removal of hydrophobic and aromatic chemicals through hydrophobic interaction with the hydrophobic regions and π–π interaction . In addition, studies also showed that the DOMs removed by granular activated carbon or biological activated carbon pretreatment were composed mainly of hydrophobic and biodegradable components, while had limited or no removal of hydrophilic components. , This was consistent with the results obtained here that GUSB pretreatment contributed to the reduction of DOM, especially the hydrophobic components. When treating the effluent of GUSB using coagulation, a similar trend was observed as compared to the direct coagulation of raw water.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…When using granular activated carbon as the substrate in the biofilter, the intrinsic composition of the carbon backbone of activated carbon favors the removal of hydrophobic and aromatic chemicals through hydrophobic interaction with the hydrophobic regions and π–π interaction . In addition, studies also showed that the DOMs removed by granular activated carbon or biological activated carbon pretreatment were composed mainly of hydrophobic and biodegradable components, while had limited or no removal of hydrophilic components. , This was consistent with the results obtained here that GUSB pretreatment contributed to the reduction of DOM, especially the hydrophobic components. When treating the effluent of GUSB using coagulation, a similar trend was observed as compared to the direct coagulation of raw water.…”
Section: Resultssupporting
confidence: 89%
“…41 In addition, studies also showed that the DOMs removed by granular activated carbon or biological activated carbon pretreatment were composed mainly of hydrophobic and biodegradable components, while had limited or no removal of hydrophilic components. 42,43 This was consistent with the results obtained here that GUSB pretreatment contributed to the reduction of DOM, especially the hydrophobic components. When treating the effluent of GUSB using coagulation, a similar trend was observed as compared to the direct coagulation of raw water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One is a water temperature in distribution networks as abovementioned, and another one is a water type. The water samples purified from surface water, which has relatively high content of hydrophilic organics such as polysaccharides rather than humic substances (Jo 2008), were used for all the regrowth experiments here; therefore, the curves should be applied to the same type of water. At the same time, this investigation indicated that AOC removal during water treatment processes should be significantly enhanced prior to minimization of chlorine residual because current AOC in finished water treated by typical advanced processes in Japan was reported to be more than 50 μg C/L (Ohkouchi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Raw water for WTP-A is piped from Lake Biwa. Jo (2008) identified that the water of Lake Biwa had a unique DOM profile containing a high percentage of hydrophilic organics by a comprehensive fractionation technique. The water samples after 5 min flashing were collected in carbon-free glass bottles prepared by thermal treatment at 550°C for 4 h. The samples for analyses were stored under refrigerated conditions and processed within 4 h after sampling.…”
Section: Water Samplingsmentioning
confidence: 99%